TORAKOCHIRURGIADo NSCLC patients become sensitive to second-line erlotinib treatment after previous radiotherapy? - Krawczyk, Paweł; Kowalski, Dariusz M.; Wojas-Krawczyk, Kamila; Krzakowski, Maciej; Milanowski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background : Erlotinib is an EGFR tyrosine kinase inhibitor (EGFR-TKI) that has shown activity in recurrent NSCLC. One could speculate that sensitivity to erlotinib is dependent on the activated form of EGFR gene mutation in tumour cells. The radiation-induced activation of the EGFR pathway and EGFR gene mutation in cancer cells could arouse the response to EGFR-TKI agents. Aim : The aim of the study was to evaluate the effectiveness of erlotinib in second- and third-line therapy according to the type of first-line therapy. Material and methods : 102 patients with recurrent NSCLC, who had erlotinib administered in second- and third-line therapy, were divided into two groups: group A – included patients treated first-line with a combination of thoracic radiotherapy and cisplatin-based chemotherapy (n = 40); group B – patients treated with chemotherapy alone (n = 62). The efficacy of erlotinib was analysed based on chi-square, Cox logistic regression and Kaplan-Meier tests. Results : Disease control and survival longer than 6 months during erlotinib administration were observed significantly more frequently in patients from Group A than from Group B (p < 0.05 and p < 0.005, respectively). Median time of overall survival was 16 months for Group A and only 5 months for Group B. Moreover, probability of survival was significantly higher in Group A than in Group B (p < 0.005, HR = 2.179, 95% CI: 1.339-3.546). Based on the Cox regression model, among 6 other prognostic factors, no application of radiotherapy in first-line treatment had a significant impact on the reduction of overall survival (p < 0.005, HR = 2.636, 95% CI: 1.385-5.015). Conclusions : Our observations indicate that application of radiotherapy in first-line treatment has predictive rather than prognostic value for the efficacy of erlotinib second- or third-line therapy.